Consequências econômicas do contrabando e descaminho no Brasil entre 2015 e 2022 - Sousa, Carlos Alberto Sombra de (Brasil, 2024)
The study of the economic consequences of smuggling and embezzlement in Brazil between 2015 and 2022 is of paramount importance, given its comprehensive impact on the country’s economy. These illegal activities, which involve the entry of goods without due payment of taxes, result in significant losses for the State and promote unfair competition with legal products. Factors such as the fragility of borders, corruption and high tax burden contribute to the increase of these illegal practices. The negative impacts include the loss of tax collection, harming investments in crucial areas such as health and education, as well as negatively affecting national companies, which may lead to the closure of companies and loss of jobs. In addition, smuggling and embezzlement are associated with increased crime and the financing of illicit activities, such as drug trafficking. The government has implemented actions to combat these illegal practices, including police operations, strengthening border enforcement and awareness campaigns. However, challenges such as lack of financial resources and complexity of the problem persist, requiring international cooperation. Future perspectives involve public policies that simplify the tax burden, strengthen enforcement and intensify awareness campaigns. The fight against smuggling and embezzlement is essential not only to preserve tax collection, but also to ensure public safety, consumer health, an equitable business environment and effective international cooperation.